Building Logic Gate Circuits in Python - Dumka, Pankaj (Mathematics and Computer Science: Contemporary Developments Vol. 5, 2024)
This paper presents the development of a Python module designed for various Logic Gates. Three circuits were built using the functions defined in Python for the logic gates, and the outcomes were found to align completely with those reported in the literature. The circuits were tested with different inputs obtaining the expected outputs.